Outside in - Ellis, Sarah, 1952- (Toronto ; Berkeley : Groundwood Books, House of Anansi Press, 2014)
"Lynn's own life is full with choir practice, school, shopping for the perfect jeans, and dealing with her free-spirited mother. Then one day her life is saved by a mysterious girl named Blossom, who introduces Lynn to her own world and family who are both more bizarre, yet somehow more sane, than Lynn. Blossom's own family is a small band of outcasts and eccentrics who live secretly in an ingenious bunker beneath a city reservoir. Lynn is enchanted and amazed. But when she inadvertently reveals their secret, she is forced to take measure of her own motives and lifestyle, as she figures out what it really means to be a family and a friend. This novel is smart, rich, engaging and insightful." -- Provided from publisher.
Keywords: Underground homeless persons -- Fiction; Underground areas -- Fiction; Homeless girls -- Fiction; Friendship -- Fiction; Underground homeless persons -- Juvenile fiction; Underground areas -- Juvenile fiction; Homeless girls -- Juvenile fiction; Friendship -- Juvenile fiction; Friendship; Homeless girls; Underground areas; Underground homeless persons; Fiction; Juvenile works